Chemical Biology Toolkit for DCLK1 Reveals Connection to RNA Processing. Issue 10 (15th October 2020) - Liu, Yan; Ferguson, Fleur M.; Li, Lianbo; Kuljanin, Miljan; Mills, Caitlin E.; Subramanian, Kartik; Harshbarger, Wayne; Gondi, Sudershan; Wang, Jinhua; Sorger, Peter K.; Mancias, Joseph D.; Gray, Nathanael S.; et al.
Summary: Doublecortin-like kinase 1 (DCLK1) is critical for neurogenesis, but overexpression is also observed in multiple cancers and is associated with poor prognosis. Nevertheless, the function of DCLK1 in cancer, especially the context-dependent functions, are poorly understood. We present a "toolkit" that includes the DCLK1 inhibitor DCLK1-IN-1, a complementary DCLK1-IN-1-resistant mutation G532A, and kinase dead mutants D511N and D533N, which can be used to investigate signaling pathways regulated by DCLK1. Using a cancer cell line engineered to be DCLK1 dependent for growth and cell migration, we show that this toolkit can be used to discover associations between DCLK1 kinase activity and biological processes. In particular, we show an association between DCLK1 and RNA processing, including the identification of CDK11 as a potential substrate of DCLK1 using phosphoproteomics. Graphical Abstract: Highlights: Overexpression or DCLK1 in DLD-1 cells results in DCLK1-dependent growth Genetic or chemical ablation of DCLK1 activity inhibits DCLK1-transformed cell growth The DCLK1 mutation G532A results in DCLK1-IN-1-resistance DCLK1 inhibition decreases RNA processing and other cellular processes Abstract : DCLK1 overexpression occurs in cancer, suggesting that DCLK1 is a therapeutic target. We report a tool kit for the study of DCLK1, including engineered DCLK1-dependent cancer cells, a DCLK1 inhibitor, and DCLK1 mutations that ablate kinase activity or confer drug resistance. We found a new association between DCLK1 and RNA processing.